Corporate Governance and Corporate Social Responsibility. - Koperunthevy, K.; Vijayarani, K. (Annamalai University, India, 2012)
The study investigates the relationship between corporate governance and corporate social responsibility based on theoretical background. The corporate governance system is concerns the distribution of rights and responsibilities among different parties among the internal participants of an entity. It concerns the value creation and wealth distribution. For the long - term purpose the survival of an entity depends on the sustainability. The sustainability is determined by the utilization of internal as well as external resources. Therefore, the corporate governance should turn its concerns on corporate social responsibility (CSR). The concept of CSR consider sustainability of an entity through satisfy and safety of all stakeholders of an entity. The stakeholder’s theory suggested that the firm should consider all stakeholders’ benefit for sustainability. Therefore, the study concludes that corporate governance and CSR are interrelated for the successful performance and survival of an entity.
Keywords: Corporate governance; CSR; Share holders; Stake holders; Value; Wealth; Sustainability